Support of decision in buildings refurbishment with a change of utility - Radziejowska, Aleksandra (Array, 2020)
Construction objects, including buildings, are characterized by a long period of use resulting from the properties of structural and material solutions properly designed, constructed and operated. Practice shows that functional aging of buildings is faster than technical. Therefore, for these reasons and taking into account current socio-economic concepts (sustainable development, preservation of cultural heritage, economic, location reasons, etc.) buildings that have ceased to perform their current function are subject to renovation and / or refurbishment, enabling them to perform new functions compatible with social needs: public and commercial. The choice of new functions cannot be accidental. The decision-making process regarding the refurbishment of a building with a change of utility function is subject to high economic risk, which is why it should be carried out using a methodology that ensures a holistic approach. The paper proposes a methodology of functional and functional programming in the pre-investment phase of project preparation using multi-criteria analysis of the utility function selection. The methodology is illustrated by an example of the choice of function in the adaptation of a post-production building from public resources.